Viability and Antibacterial Activity of Bifidobacterium bifidum in Fermented Robusta Coffee for Diarrhea Treatment - Miksusanti; Elsa Fitria Apriani; Dimas Nur Hidayat (Universitas Airlangga, 2022)
Background: Diarrhea can be treated with probiotic bacteria such as Bifidobacterium bifidum, which decreases the intestinal environment's pH to become acidic so that pathogenic bacteria cannot thrive. Objective: To make fermented coffee that can increase the number of probiotic bacteria Bifidobacterium bifidum and has antidiarrheal activity against pathogenic bacteria Escherichia coli. Methods: Robusta coffee (20.25% and 19.75%) was fermented using Saccharomyces cerevisiae, and then the probiotic bacteria Bifidobacterium bifidum was added. Unfermented coffee was compared with the same concentration (20.25% and 19.75%) to obtain four formulas. Organoleptic panelists tested all formulas to determine the best formula for fermented and non-fermented coffee. The number of Bifidobacterium bifidum and antibacterial activity was calculated on the optimum formulation using the Total Plate Count and Disc Diffusion Method. Result: The optimum formula obtained at fermented and unfermented coffee concentration was 20,25%. The number of probiotic bacteria Bifidobacterium bifidum growing in fermented and non-fermented coffee was 7.3 x 108 ± 32.4 and 3.1 x 108 ± 30.7 (p < 0.05). The diameter of the inhibition zone of the best fermented and non-fermented coffee was 11.5 ± 0.5 mm and 8.5 ± 0.5 mm, respectively (p < 0.05). Conclusion: Fermented coffee can increase the growth of the probiotic bacteria Bifidobacterium bifidum and has strong antibacterial activity against Escherichia coli bacteria.